Direct Speech in Acts and the Question of Genre - Pervo, Richard I. 1942-2017 (2006)
G. Horsley and C. Hemer noted, on the basis of statistical comparison, that the large quantity of direct speech in Acts is atypical of ancient historiography. This study builds upon their research by expanding the repertory to include representatives of ‘popular fiction’. Quantitative analysis reveals that direct speech is one characteristic of popular literature and that, in this respect, Acts is more like popular narrative than learned historiography. This finding contributes to, but does not resolve, the question of the genre of Acts.